Establishment and Genetic Profiling of Platinum/Taxane Doublet-Resistant Cells Generated by Hybridizing Single Resistant Cells - Seiji Isonishi; Rika Saito; Noriko Yamaguchi; Saburo Saito (Clinical and Experimental Obstetrics & Gynecology)
Background: Current standard chemotherapy for gynecologic malignancies consists of platinum agent and taxane though, many patients experience the relapse of disease with drug resistance making the following therapy unsuccessful. It’s a compelling question whether the mechanisms of doubly resistance is a simple combination of single agent resistance or whether the core novel mechanism common to platinum and taxane resistance stands out as a result of combination therapy. The purpose of this study is to establish the doublet drug resistant cell line and to find its genetic characteristics. Methods: Platinum/taxane doublet resistant cell lines (F3 and F4) were generated by hybridizing two independent, platinum or taxane resistant subline (C13 or PX24) stemmed from grand parental ME180 cells. The resistant cells were selected through repeated exposure to cisplatin and paclitaxel. For the assessment of drug sensitivity, colony forming assay was used. For the gene expression analysis, genome-wide expression profiling was done using the Human Genome U133A Array. Protein-protein interaction network (PPI) scaffold networks were retrieved from the Search Tool for the Retrieval of Interacting Genes database and, for the enrichment of pathway analysis, WebGestalt was used. Results: Colony forming assay showed C13 was 5.8-fold cisplatin resistant while PX24 was 5.3-fold paclitaxel resistant compared with parental ME180 cells. F3 and F4 acquired resistance to cisplatin and paclitaxel by 8.3/4.9- and 3.7/3.3-fold (F3/4) respectively. Microarray analysis demonstrated, out of 22284 genes, 103 genes were >4-fold up-regulated in F3/4 and 33 (32%) were identified as simultaneously upregulated genes (SUG) in C13, PX24 and F3/4. The Protein-protein interaction analysis of 33 SUG displayed a scaffold network pivoting aldo-keto reductase 1C1 (AKR1C1), aldo-keto reductase1C2 (AKR1C2) and aldo-keto reductase1C3 (AKR1C3). The enrichment pathway analysis demonstrated AKR1C gene family anchored to molecular function of oxidoreductase and aldo-keto reductase activity and biological process of daunorubicin and doxorubicin metabolism. Conclusions: We report here the establishment of doubly drug-resistant hybridoma to platinum and taxane. Analysis of SUG indicated the AKR1C gene family plays a key role for doubly resistant mechanism that would be possible targets for therapeutic strategies.